Nanoencapsulation of Colchicum speciosum for Alleviating Lower Back Pain - Beiranvand, Siavash; Kiabi, Farshad Hassanzadeh (Current Nanomedicine, 2025)
This review focuses on the use of Colchicum species that have been capsuled to treat lower back pain. Low levels of physical activity produce atypical spinal loading, which increases the risk of discomfort and damage. Acetylcholine (AChE inhibitors acetylcholinesterase AChE-I) has a crucial role in the development of amyloid- plaques, one of the disease's main pathogenic processes, and in boosting psychological function. To increase the natural preservatives in food, research on the encapsulation of phytochemicals has been employed to create nanoparticle delivery systems for a combination of terpenes that have been isolated from plants. For the administration of formulations containing encapsulated plant extracts, dermal and oral routes are used. The current strategies of encapsulation should be enhanced, as well as techniques to achieve the goal.
Keywords: dermal routes